Current research on carbetocin and implications for prevention of postpartum haemorrhage - Fiona J. Theunissen; Lester Chinery; Yeshita V. Pujar (BMC, 2018)
Abstract Background Postpartum haemorrhage (PPH) is the leading cause of maternal mortality in low-income countries and is a significant contributor to severe maternal morbidity and long-term disability. Carbetocin may be an underused uterotonic for prevention of PPH. A number of studies are being conducted that may challenge the place of oxytocin as the first choice of uterotonics for prevention of PPH. This paper describes the current research into carbetocin and ranking of effectiveness of uterotonics that may provide important new information to assist healthcare decision makers to ensure that women receive an effective uterotonic for prevention of PPH. Methods We searched the WHO International Clinical Trials Registry Platform for current studies on effectiveness of carbetocin for prevention of PPH following vaginal delivery with sample sizes large enough to provide quality evidence to support potential changes to international guidelines. We also searched the Cochrane Library for current systematic reviews including carbetocin used in prevention of PPH. Results Susceptibility to degradation from exposure to heat is one of the key causes of reduced effectiveness of oxytocin in preventing PPH from uterine atony. Although heat stable and effective in preventing PPH, misoprostol is also subject to degradation due to exposure to moisture and produces some side-effects. Other uterotonics (including ergometrine and combinations of oxytocin, ergometrine and misoprostol) are also available and used with varying safety and effectiveness profiles and quality issues. Efforts to reduce maternal mortality from PPH include research studies seeking to identify safe, stable, effective uterotonics. Heat stable carbetocin is the subject of two major clinical studies into its effectiveness in preventing PPH following vaginal deliveries, information that could expand its application for prevention of PPH. Conclusion Heat stable carbetocin is being investigated as a potential alternative to oxytocin. This paper describes two current clinical trials on carbetocin and a network meta-analysis ranking of all uterotonic agents, including carbetocin, which combined may provide evidence supporting expansion of the use of the heat stable formulation of carbetocin in PPH prevention.